Pengaruh Kelerengan terhadap Perkembangan Lahan Terbangun di Kabupaten Serang, Provinsi Banten - Nagara, Rakyan Paksi; Wibowo, Adi (P4W IPB, 2024)
The flow of urbanization is unstoppable as the population grows, which is followed by an increase in the need for built-up land such as housing, commercial centers, public services, industry. Meanwhile, each land has different characteristics to support these human activities. In land suitability studies, the slope is an important factor and is always involved. This study aims to determine the influence of slope on the development of built-up land in Serang Regency, as one of the areas with a high population growth rate and a variety of regional morphologies. Land cover/land use change analysis was used to determine the spatial distribution of additional built-up land in the period 2019-2023 and 2023-2031. 87% of the additional built-up land in 2019-2023 is located in areas with slopes of 2-15%. Then based on the Serang Regency Regional Spatial Plan 2011-2031, as much as 84% of the additional built-up land is in areas with slopes of 2-15%. This shows that the slope aspect has had a significant influence on the development of Serang Regency, where more than 80% of the additional built-up land has been located in zones that are safe from land slide.